Peningkatan Penguasaan Materi Kalor Dan Perpindahannya Melalui Implementasi Model Pembelajaran Problem Posing - Sapulete, Heppy; Nirahua, Juliana; Barus, Carolina Sri Athena (Physikos: Journal of Physics and Physics Education, 2022)
This study aims to describe the improvement of the ability to master heat material and its transfer by implementing a problem posing learning model in grade VII students of SMP Santo Andreas Ambon. This research uses quantitative descriptive research methods. The instruments used are the initial test instrument and the final test. The results of this study showed that the initial ability of students in heat and transfer material was very low with an average score of 43.5 achievement being in the qualification of failing. After learning with the problem posing learning model, the average score of the final ability of students was 84.2 with good qualifications. The increase in student material mastery after applying the problem posing learning model is in the high category of 65% and the medium category of 35% with an average increase (N Gain) of 0.70% with moderate qualifications. Thus, it can be concluded that learning using the problem posing learning model can improve the mastery of heat material and its transfer to grade VII students of SMP Santo Andreas Ambon.